Overcoming nutrient limitations for cell-based production of influenza vaccine - Liu, Xu-Ping (Hum Vaccin Immunother, 2015)
Metabolic analysis for medium optimization represents a very useful strategy in the process development of production of vaccines in cells. During influenza vaccine production, viruses hijack host cells and take advantage of host's metabolism. As a consequence, the nutritional demand of host cells should undergo a profound change, and usually more nutrients such as glucose and amino acids should be consumed. As such, the maintaining media used in virus production processes often cannot provide sufficient nutrients, and novel methods are urged to be established to address this severe issue of nutritional limitation. A detailed study on impacts of influenza virus on cell death and metabolism, with a profound analysis of nutritional requirements during virus production process, followed by a rational medium optimization is expected to be the most straightfoward and effective strategy. This would ensure a balanced and adequate nutritional supply, which should minimize cell death and improve both cell-specific virus yield and total influenza virus production. Such a metabolic analysis-based medium optimization would lay a solid foundation for the development of cell culture technology in influenza vaccine production.